The effect of endurance training and curcumin supplement on lung HIF- α1 levels in rat exposed to lead acetate - ابوالقاسم گرجی; شادمهر میردار; سعید نظری; مهدی هدایتی (فیزیولوژی ورزش و فعالیت بدنی)
Background and purpose: Hypoxia inducible factor-1α (HIF- α1) as a key regulator of molecularresponses to hypoxia is regarded as a mediator for a large scope of cellular and physiological mechanismsnecessary for compatibility with decrease of oxygen. The aim of present research was to study the effet ofendurance training, curcumin supplement and lead on the lung HIF- α1 levels.Methods: Sixty 50-day- oldmale wistar rat are divided to two control groups, two exercise groups (exercise + lead and exercise +lead + supplement) and two groups without exercise (curcumine + lead and lead). The exercise includesrunning with speed of 15 to 22 meter per minute on the animal treadmill without slope for 25 to 64minutes for eight weeks. After the eight weeks of exercise and seventy-two hours after the last exercisethe rat are killed and the intended tissues are used for measuring HIF- α1 using kit and ELISA method.Kolmograph Smirnov test and LSD test in the level P < 0.05 are used to analyze the findings of theresearch. Results: The results of the research indicate intra peritoneum injection of lead increase theamount of lead in the lead group. A significant increase in the level of HIF- α1 in lung is seen in thecontrol group in contrast to lead group and exercise + lead + supplement group and in vehicle group incontrast to exercise + lead + supplement group and in lead + supplement group in contrast to exercise +lead + supplement group. A significant decrease in the level of HIF- α1 in lung is seen in lead group incontrast to exercise + lead group and in exercise + lead + supplement group in contrast to exercise + leadgroup. The results of the research indicate intra-peritoneum injection of lead increase the amount of leadin the lead group. A significant decrease in the level of HIF- α1 in liver is seen only in lead group incontrast to exercise + lead + supplement group and lead group. Conclusion: The results of this researchindicate regular endurance exercise can counteract the effects of stat lead and it can be regarded as auseful solution for pollution caused by lead. Also according to previous research the presence curcumin inof the train and lead, are expected to reduce and inhibit HIF- α1 but there was no such thing, in lungtissue combined exercise, curcumin, lead, HIF- α1 is increased because it can be attributed to the dose.